Comissões Próprias de Avaliação: controle ou emancipação? - Carvalho, Erivanio da Silva (2009)
The purpose of the present work is to investigate how institutional self-evaluation has been conducted by Evaluation Commissions (Comissões Próprias de Avaliação - CPA). I analyzed how that process has been developed based on the following leading question: in the process of institutional self-evaluation, are the internal commissions guided by controlling actions or do they make room for emancipation? For theoretical support, I researched several authors, such as: José Dias Sobrinho, Paulo Freire, Ana Maria Saul, Isabel Franchi Cappelletti, Charles Hadji, Jean-Jacques Bonniol, Michel Vial, Pedro Demo and Antonio Faundez. The methodological approach for the research was qualitative, consisting of interviews with commission coordinators who explained the development of self-evaluation process and made their point on the current external evaluation proposed by MEC. The results showed that the evaluation questions and actions are restricted to the members of Evaluation Commissions (CPA) disregarding the participation of the community. As far as autonomy is concerned, the CPA coordinators think the work conditions are satisfactory; however, the practices regarding the evaluation pattern ignore the participation, which characterizes the process of institutional self-evaluation as a controlling procedure